Extravasation of Antineoplastic Agents: Prevention and Treatments - Boschi, Rita (Pediatr Rep, 2012)
The extravasation of antineoplastic agents is an unwanted and distressing situation that can easily occur. It may cause severe and irreversible local injuries. Left untreated, vesicant chemotherapy extravasation can potentially cause tissue necrosis, functional impairment and permanent disfigurement. This article provides a review of current literature regarding recommendations on the prevention and treatment of extravasation of antineoplastic agents.